[tex]\vec r(t)=3t\,\vec\imath-4t\,\vec\jmath[/tex]
[tex]\implies\left\|\dfrac{\mathrm d\vec r(t)}{\mathrm dt}\right\|=\|3\,\vec\imath-4\,\vec\jmath\|=\sqrt{3^2+(-4)^2}=5[/tex]
The line integral of [tex]f(x,y)[/tex] along the curve [tex]C[/tex] parameterized by [tex]\vec r(t)[/tex] is
[tex]\displaystyle\int_Cf(x,y)\,\mathrm ds=\int_{-2}^{-1}f(3t,-4t)\left\|\dfrac{\mathrm d\vec r(t)}{\mathrm dt}\right\|\,\mathrm dt=-20\int_{-2}^{-1}te^{9t^2}\,\mathrm dt[/tex]
Substitute [tex]u=9t^2[/tex] so that [tex]\mathrm du=18t\,\mathrm dt[/tex]. Then
[tex]\displaystyle\int_Cf(x,y)\,\mathrm dS=-\frac{20}{18}\int_{36}^9e^u\,\mathrm du=\frac{10}9\int_9^{36}e^u\,\mathrm du=\boxed{\frac{10}9(e^{36}-e^9)}[/tex]